Molecular Mechanism of Anti-Colorectal Cancer Effect of Hedyotis diffusa Willd and Its Extracts - Wu, Zihong; Yin, Bei; You, Fengming (Frontiers in Pharmacology, 2022)
With the sharp change of our diet and lifestyle, the incidence of Colorectal cancer(CRC) is increasing among young people, and which has become the second most common malignant tumor worldwide. Although the current treatment of CRC is getting updated rapidly, recurrence and metastasis are still inevitable. Therefore, new anti-cancer drugs are needed to break existing limitations. In recent years, Hedyotis diffusa willd(HDW) extracts have been proved to demonstrate excellent anti-colorectal cancer effects and have been widely used in clinical practices. In this review, we aim to explore the advantages, potential signaling pathways and representative active ingredients of HDW in the treatment of CRC from the perspective of molecular mechanism, in order to provide new ideas for the future treatment of CRC.